Risk factors of SARS‐CoV‐2 seroprevalence among hospital employees in Italy: a single‐centre study. Issue 7 (26th April 2021) - Daperno, Marco; Guiotto, Cristina; Casonato, Ines; Pagana, Guido; Micalizzi, Sergio; Azzolina, Maria C. R.; Norbiato, Claudio; Cosseddu, Domenico; Rocca, Rodolfo; ,
Abstract: Background: The SARS‐CoV‐2 outbreak early in 2020 overwhelmed the Italian national health system, and hospitals were considered places at high risk of spreading the infection. We explored specific antibody seroprevalence of all employees at a single hospital in the epicentre of the outbreak, to identify areas of risk in nosocomial setting and to evaluate the usefulness of antibody testing. Aims: Aim of this study was to explore SARS‐CoV‐2 seroprevalence in a single hospital workers cohort. Methods: All hospital workers were invited to fill in a questionnaire and undergo a blood test for SARS‐CoV‐2 IgG, using two commercial tests (DiaSorin and Abbott). Seropositivity was determined overall and according to demographic and occupations characteristics, for both tests singly and combined. Results: The study enrolled 1562 hospital workers (95% of the eligible population). Overall, 153 (9.8%) participants were positive for SARS‐CoV‐2 IgG on DiaSorin test, and 150 (9.6%) were positive on Abbott test; both tests were positive in 123 (7.9%) cases and at least one was positive in 180 (11.5%) cases. Factors associated with SARS‐CoV‐2 seropositivity included: being a smoker, working in emergency or medicine departments, being a healthcare practitioner, self‐reporting a relative with COVID‐19 or symptoms suggestive of COVID‐19, and having undergone a nasopharyngeal swab test. The tests were accurate in discriminating infected cases, with an area under the receiver operating characteristic curve of 0.867 using manufacturer‐suggested cut‐offs and 0.929 using optimised cut‐offs. For discriminating symptomatic subjects, this value was 0.915 using optimised cut‐offs. Conclusions: Seroprevalence for SARS‐CoV‐2 in this population of hospital workers was overall about 10%, with an excess prevalence in roles and departments associated with contacts with COVID‐19 patients.